Mechanical Properties of Ramie/Hemp Hybrid Composites Influenced by Stacking Arrangement and NaOH Treatment - Mohamad Reda A. Refaai; Stalin Narayanasamy; V. Chittaranjan Das; D. V. S. S. S. V. Prasad; N. Nalini; Subash Thanappan (Advances in Polymer Technology)
This research is aimed at seeing how different stacking sequences and chemical treatments impact the mechanical characteristics of ramie–hemp composites. Hand-lay-up procedures were used to create a blend of woven ramie and hemp fibers. The woven ramie was treated with a diluted 6% sodium hydroxide (NaOH) solution to compare the mechanical properties of preserved and unpreserved ramie hybrid composites. According to the findings, the tensile properties of hybrid composites are better in three-layer composites than in four-layer composites. Hemp-based hybrid composites outperform other hybrid composites in terms of mechanical properties. Hybrid composites that have been treated have better tensile and flexural properties than hybrid composites that have not been treated. The sample H/R/H/R was found to have the best impact characteristics. This research is part of a more extensive investigation of hybrid composite’s application in high-velocity impact applications.